Subacute Toxicity of Chitosan Oligosaccharide in Sprague-Dawley Rats - Kim, Se-Kwon; Park, Pyo-Jam; Yang, Hyun-Pil; Han, Sang-Sup (Arzneimittelforschung, 2001)
A subacute oral toxicity study of chitosan oligosaccharide was performed in Sprague-Dawley rats of both sexes. Each 36 male and female rats were administered by gavage with 500, 1,000 and 2,000 mg/kg/day for 4 weeks (7 days/ week), respectively. Examinations regarding clinical signs, body weights, hematological and biochemical parameters, and histopathological examinations were carried out. There were no significant differences in behavior or external appearance, body weight and food consumption between control and treated rats. In addition, no significant differences in urinalysis, hematology, blood biochemistry, relative organ weights and histopathological findings were found in both control and treated rats. In conclusion, it was suggested that subacute toxicity of chitosan oligosaccharide was low and the no-observed adverse effect level was considered to be over 2,000 mg/kg in rats.
Keywords: Chitosan oligosaccharide, rat, subacute toxicity